Climate change - reconciling islamic ethics and practices - : a case study on Indonesia - Siti Elmi Atan (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2021)
Islam propounds high standards for the protection of the environment. The Qur’ān explains the purpose of man’s creation as khalifah on earth entrusted with its protection and Muslims as exemplifying the best community for other communities to emulate. However, countries with the highest contribution to global carbon emissions are countries where Islam has the highest number of followers. Indonesia, a country with the highest Muslim population, contributes to a high level of carbon emissions. At the same time, it is also one of the countries most vulnerable to the adverse effects of climate change. Based on the Climate Change Performance Index, Indonesia ranked thirty-eighth and is considered a “low-performing” country in its overall scorecard rating. Despite the country having the most ambitious greenhouse gas [GHG] emissions targets, deforestation in Indonesia continues to grow at an alarming rate. This paper studies the meaning and root causes of climate change, the ethical guidance from Qur’anic verses and ahadith regarding the protection of the environment. The paper examines the extent of the Indonesian Muslim community’s actions that contribute towards climate change contrary to scriptural guidance. It analyses the actions that have been initiated at national level in Indonesia and those initiated by grassroots communities towards the efforts to reverse climate change.